Pertumbuhan Bibit Cendana (Santalum album L.) dengan Inang Primer pada Intensitas Radiasi Berbeda - Yudi Riadi FanggidaE; Impron Impron; Tania June (Institut Pertanian Bogor, 2020)
The primary host of sandalwood seeds (Santalum album L.) which is widely used in the nursery process is Alternanthera sp. However, the local name given to this primary host is same as that given to Portulaca sp. The same local name for these two-different species may cause mistakes in the use of the primary host during the cultivating process of sandalwood. Meanwhile, the ability of the Portulaca sp. as the primary host is unknown. Information about the right radiation intensity of the sandalwood seedling is still limited. The study aims to analyze the growth of sandalwood seedlings grown with primary host of Alternanthera sp. and Portulaca sp. at different radiation intensities. The completely randomized design with two treatments factor were used, namely differences in shade levels (without shade, 25, 50, and 75%) and differences in the types of primary hosts. The result showed that the primary hosts of Alternanthera sp. have the best growth for sandalwood seeds compared to sandalwood seedlings planted with Portulaca sp. The shading must be adjusted to the type of primary host. Sandalwood seeds grown with Alternanthera sp. as primary hosts grow best at 50% and 75% paranet shade conditions, in radiation range of 9.86–12.17 MJ/m2/day. Sandalwood seeds planted with Portulaca sp. as a primary host grow best in 25% paranet shade, that is at average radiation of 13.62 MJ/m2/day. The use of Alternanthera sp. and shade provision (50–75%) is highly recommended in sandalwood seedlings. Keywords: haustoria, hemiparasite, primary host plant, sandalwood, symbiosis